Solaris and the Dao: The Reception of Stanislaw Lem’s Novel in the Sinophone World - Wybieralska, Zofia Anna (Poznańskie Studia Polonistyczne. Seria Literacka, 2021)
The most popular science fiction novel written by the Polish author Stanisław Lem, Solaris, was published in 1961. Although it was translated into English as early as 1970, the book was unknown to the Sinophone readers until 2003, when the first translation from English into Chinese was published, most probably following the popularity of the resounding Hollywood film adaptation from 2002. Still, Suolalisi Xing (which can be translated as ‘Solaris Star’) did not attract broader audiences in China or Taiwan, at least not until the third version of the novel, translated directly from Polish into Chinese, saw the light of day in 2010. The appearance of this translation coincided with the beginning of a New Golden Era of Chinese and Taiwanese science fiction, which undoubtedly had a significant influence on the positive re-reception of Solaris. In the paper, the author focuses on the philosophical aspect of Lem’s work and investigates which themes and concepts present in Solaris caught the imagination of Chinese-speaking readers. The author wants to show how this reception, while coming from a different historical, cultural, and linguistic background, can enrich our understanding of the novel and introduce a new way of looking at the important existential questions stated by the writer.